Level of Pollution and Determining Factors of Water Health in Citarum River, Muara Gembong, Bekasi, West Java - Bayu Awifan Dwijaya (Universitas Tidar, 2022)
The restoration of water quality needs to be monitored on the rivers in Indonesia. Land occupation and land conversion are the main problems that have an impact on the handling of water quality in the Muara Gembong area. The research location is located in Muara Gembong District, Bekasi Regency, West Java. Water quality testing in this study was carried out directly in the field using in situ digital measuring instruments including pH, air temperature, DO, TDS, Phosphate, Brightness and Salinity. Meanwhile, the TSS and BOD parameters were tested in the laboratory at the Secretariat of the Indonesian Biodiversity Conservation Unit (IBCU). The results of the Pollution Index showed that the research location was divided into 2 groups, namely moderate pollution Beting Outfall, Bungin Outfall and Upstream), light pollution (Middle Stream, Bendera Outfall, Outfall Bloom and Outfall Herons). The results of PCA analysis with a variance value of 40.8% showed that the location of the study was holistic by BOD value, phosphate content and salinity as environmental parameters that determined environmental conditions.